PEMBERDAYAAN MASYARAKAT DESA PULO PANJANG MELALUI DIVERSIFIKASI PANGAN DENGAN SINGKONG: LANGKAH AWAL MENUJU KEMANDIRIAN PANGAN DESA - Rafillah, Rahadatul Aisyi; Veline Angela Natasya; Regaf Fahmi Ilmi; Indra Lesmana; Selfi Auliansyah; Mohamad Haikal; Cindy Wulandari; Kayla Novia Ramadhani; Muhammad Nazil Fikri Zamzamie; Saidah Rahmah; Wida Octaria; Anisa Khoirul Jannah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Indonesia is one of the countries that still shows high dependence on one type of food commodity, namely rice. This dependence has implications for the low diversity of essential nutritional intake and increases vulnerability to food supply instability, both at the local and national scales. In this context, the issue of food security becomes increasingly crucial, considering that food is a fundamental human right for the welfare of citizens. Food security is also a strategic aspect in regional economic development, especially in rural areas. One approach that can be taken to strengthen food security is through the utilization of local food ingredients as a diversification effort. In Indonesia, cassava (Manihot esculenta) is one of the local commodities that has the potential as an alternative carbohydrate source to replace rice. However, public knowledge and awareness, especially in villages, of the importance of food diversification are still limited. This study aims to analyze the effectiveness of the cassava-based food diversification socialization program implemented in Pulo Panjang Village, Puloampel District, Serang Regency. This analysis is expected to contribute to formulating strategies to increase the utilization of local food ingredients as part of sustainable food security development.